Comparative study about some eating habits in six countries: eating out and fast food consumption - Guiné, Raquel (2020)
Poor diets have proven very detrimental for the maintenance of good health and eating an excessive amount of fast food and highly processed meals can harm the general health status of the population. Hence, this work investigates the habits related to eating outside the home and frequency of eating fast food meals in participants from six different countries. A cross-sectional descriptive study was undertaken on a sample of 4,904 adult participants. For the data treatment, basic statistics were complemented with tree classification analysis, using the CRT algorithm. This study concluded that in the sample under study the frequency of eating out of home was in general low, corresponding to four or fewer times per week for 71.9% of the participants, and the consumption of fast food meals was also acceptable, i.e., with a low frequency of up to two times per week in 88.6% of the respondents. The biggest differences were encountered when comparing participants from different age groups, countries or sexes, and not so much for living environment or education level. Tree classification analysis highlighted the relative importance of the considered factors for eating out and fast food meals, being country and age confirmed as the most influential factors. In the evaluated sample the incidence of eating out and fast food meals were low, which is a good indicator to contribute globally for the good health status of the participants involved in the study.